Water gas shift and sorption-enhanced water gas shift reactions using hydrothermally synthesized novel Cu–Mg–Al hydrotalcite-based catalysts for hydrogen production. (July 2021) - Lee, Chan Hyun; Kim, Suji; Yoon, Hyung Jin; Yoon, Chang Won; Lee, Ki Bong
Abstract: As the interest in environmentally-friendly energy processes increases, many studies have been focused on producing hydrogen as an alternative energy carrier via catalytic reaction processes. Among several potential reaction processes, water gas shift (WGS) reaction has been studied extensively as a typical catalytic reaction for bulk production of hydrogen. Recently, many studies have been conducted on the formation of an easily reducible active components in order to develop novel catalysts having excellent activities at low temperatures for WGS reaction. In this study, new catalysts based on hydrotalcite with unique interlayered structure were prepared by a hydrothermal synthesis and co-precipitation of copper (Cu) for active metal sites. The catalysts synthesized from different precursors showed that the reduction property of Cu was greatly changed according to the mixed oxide structure generated after calcination. Cu–MgH AlH, the hydrotalcite-based catalyst synthesized using hydroxide precursors, showed the highest redox property and the multiple analysis results confirmed that MgAl2 O4 spinel structure is attributed to form easily reducible Cu species. Based on these characteristics, Cu–MgH AlH showed excellent catalytic performance in the WGS reactions between 250 and 400 °C, and it was successfully applied to the sorption-enhanced WGS reaction using catalyst-sorbent hybrid solid pellets. Especially, the hydrotalcite-based catalyst has high potential for application to sorption-enhanced reaction processes using molten salt containing CO2 sorbents because the high reduction properties of Cu species are well maintained in the catalyst when mixed with CO2 sorbents. Graphical abstract: Image 1 Highlights: Hydrotalcite-based catalysts were fabricated by co-precipitation through hydrothermal synthesis. The intrinsic interlayered structure of hydrotalcite enhanced redox property of Cu species. The prepared catalyst-sorbent hybrid solid had good catalytic activity as well as high CO2 sorption uptake. Catalyst-sorbent hybrid solid was successfully applied in the SE-WGS reaction to produce high-purity hydrogen.